Digital planning and individual implants for secondary reconstruction of midfacial deformities: A pilot study. Issue 2 (4th February 2022) - Liokatis, Paris; Malenova, Yoana; Fegg, Florian‐Nepomuk; Haidari, Selgai; Probst, Monika; Boskov, Marko; Cornelius, Carl‐Peter; Troeltzsch, Matthias; Probst, Florian‐Andreas
Abstract: Objective: To evaluate the feasibility and accuracy of implementing three‐dimensional virtual surgical planning (VSP) and subsequent transfer by additive manufactured tools in the secondary reconstruction of residual post‐traumatic deformities in the midface. Methods: Patients after secondary reconstruction of post‐traumatic midfacial deformities were included in this case series. The metrical deviation between the virtually planned and postoperative position of patient‐specific implants (PSI) and bone segments was measured at corresponding reference points. Further information collected included demographic data, post‐traumatic symptoms, and type of transfer tools. Results: Eight consecutive patients were enrolled in the study. In five patients, VSP with subsequent manufacturing of combined predrilling/osteotomy guides and PSI was performed. In three patients, osteotomy guides, repositioning guides, and individually prebent plates were used following VSP. The median distances between the virtually planned and the postoperative position of the PSI were 2.01 mm ( n  = 18) compared to a median distance concerning the bone segments of 3.05 mm ( n  = 12). In patients where PSI were used, the median displacement of the bone segments was lower ( n  = 7, median 2.77 mm) than in the group with prebent plates ( n  = 5, 3.28 mm). Conclusion: This study demonstrated the feasibility of VSP and transfer by additive manufactured tools for the secondary reconstruction of complex residual post‐traumatic deformities in the midface. However, the median deviations observed in this case series were unexpectedly high. The use of navigational systems may further improve the level of accuracy. Abstract : To evaluate the feasibility and accuracy of implementing three‐dimensional virtual surgical planning (VSP) and subsequent transfer by additive manufactured tools in the secondary reconstruction of residual post‐traumatic deformities in the midface. This study demonstrated the feasibility of VSP and transfer by additive manufactured tools for the secondary reconstruction of complex residual post‐traumatic deformities in the midface. However, the median deviations observed in this case series were unexpectedly high. The use of navigational systems may further improve the level of accuracy.